STUDI LITERATUR: DAMPAK BENCANA BANJIR ROB AKIBAT ALIH FUNGSI LAHAN MANGROVE BAGI KEHIDUPAN MASYARAKAT - Alifya, Anida Nur; Mutaaqien, Abied Rizky Putra (Jurnal Ilmiah Sultan Agung, 2025)
The conversion of mangrove land into ponds or settlements can have a significant negative impact on tidal flood disasters. Tidal floods are an event that occurs in coastal areas due to rising sea levels that cause overflow onto land. This study aims to examine changes in the conversion of mangrove land and analyze the impacts caused by tidal floods. The research methodology used is to use literature review analysis techniques to examine the Impact of Tidal Flood Disasters Due to Conversion of Mangrove Land Functions on Community Life, which is based on the analysis of previous research journals by raising case studies, with literature review techniques to find out and evaluate previous research. Mangrove age factors, climate factors, and coastline change factors can affect the impact of tidal floods due to conversion of mangrove land functions. Keywords: : Land Conversion, Mangrove Land, Conversion of Mangrove Land Functions, Tidal Floods, Impact of Tidal Floods.